Teachers’ Awareness of the Role of EFL Learner Autonomy in Promoting Learning Outcomes - Layla Zourez , Layla (Milev Journal of Research and Studies, 2019)
Being a key concept in the field of language learning, autonomy forms the nucleus of the teaching/learning process (TLP). The learner-centered approach considers the learner as the main actor in class, and the most responsible figure for the whole process of teaching and learning. It is generally believed that learners depend more on themselves when the learning context provides opportunities and activities that meet their needs. Encouraging and incorporating elements that help in creating more autonomous language classrooms is reported to promote learning outcomes. In the present paper, the focus is put on investigating teachers’ awareness and encouragement of autonomous learning. In addition, the attempt is equally concerned with exploring their beliefs about the role of learning autonomy in fostering learning outcomes. Data was gathered relying on the questionnaire as a research tool. The findings show that EFL teachers are aware of the role of autonomous learning.